Eksplorasi Persepsi Konsumen Terhadap Strategi Price Discount (Promo Super Si Gayan) Supermarket Tiara Dewata Denpasar - I Putu Adi Surya; Candraningrat (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This research is motivated by changes in consumer behavior after the COVID-19 pandemic who are increasingly sensitive to prices and selective in responding to promotions. Tiara Dewata Supermarket in Denpasar launched the "Super Si Gayan Promo" program as a price discount strategy to attract consumer shopping interest, but there has been no in-depth academic study on its effectiveness. The purpose of this study is to explore consumer perception of the promotional program. The research uses an exploratory qualitative approach with in-depth interview methods and observation of 6 consumers who have participated in the promotion and 1 party from the management of Tiara Dewata. The results show that consumers generally value discounts as attractive incentives that increase spending value, but there are differences of opinion regarding exclusive access for members, purchase limits, and transparency of product information. This strategy also influences consumer digital behavior, such as increased visits and interaction through apps. The implications of these findings emphasize the importance of inclusive, adaptive and transparent promotions in meeting consumer expectations and building long-term loyalty in increasingly competitive retail competition.